On Some Peculiarities of Translation of Tourist Texts from Chinese into Russian - J. Zhang (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The problem of translation of tourist texts from Chinese into Russian is considered. The relevance of the work is determined by the demand for the results of cultural communication research, including those in the tourism sector, which is developed in accordance with the trends typical to international communication. It is indicated that special role in the development of tourism is played by advertising texts, in particular translated ones, which are created for travellers from other countries, including Russia. Attention is paid to the linguistic factors influencing the translation: the presence of non-equivalent language units and lexical lacunae found in the Chinese and Russian languages, differences in the structure of sentences, discursive characteristics. It is noted that the translation into Russian text as a whole should be brief, clear and emotional. It is indicated that the artistic concept of the Chinese text discourse provides such an organization of the text so that it has a specific impact - causes impressionistic subjective feeling, while the Russian text discourse is informative and striving for objectivity. The authors come to the conclusion that the in-depth analysis of language differences affecting the translation of tourist texts from Chinese into Russian allows to find the best translation strategies to enhance the effectiveness of intercultural interaction.